Multistep screening and selection of COVID‐19 convalescent plasma donors at the early stage of the SARS‐CoV‐2 pandemic: A retrospective analysis. Issue 5 (13th September 2022) - Brosig, Andreas M.; Ossner, Thomas; Pamler, Irene; Friedinger, Susanne; Bica, Adelina‐Florina; Mohrez, Morad; Tlili, Ikram; Mueller, Viktoria; Becke, Christine; Haehnel, Viola; Baeuerlein, Veronika; Stemmer, Barbara; et al.
Abstract: Background and Aims: The COVID‐19 pandemic reached Bavaria in February 2020. Almost simultaneously, Chinese physicians published reports on the first successful treatments with plasma from COVID‐19 convalescent donors. With these silver linings on the horizon, we decided to establish the manufacturing of anti‐severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibody‐containing plasma from COVID‐19 convalescent donors at our site. Here we describe our donor selection process, built from the ground up, which enabled us to cope with the immense resonance after our social media call for donors. Methods: As a first step, we created a specific questionnaire for telephone interviews applied by trained students to filter the wave of callers interested in plasma donation. Afterward, the medical staff evaluated the hotline questionnaires and chose eligible donors to be invited for on‐site donor evaluation. Data documentation was performed with MS Excel, and statistical analyses were calculated with GraphPad Prism 8. A quantitative in‐house ELISA was used to detect anti‐SARS‐CoV‐2 antibodies and determine specific titers. Results: Out of 1465 calls from potential plasma donors, we could register 420 persons with a completed questionnaire. Evaluation of questionnaires identified 222 of 420 persons as eligible for donation, and 55 were directly asked for on‐site donor qualification. Subsequently, as anti‐SARS‐CoV‐2 antibody titers ≥1:800 were required, we invited 89 of 222 potential donors for an antibody screening. This procedure resulted in another 28 potential donors for an on‐site evaluation. Finally, 12 donors qualified with a titer of 1:400 and 24 with ≥1:800. Conclusion: Identifying suitable COVID‐19 convalescent plasma donors was expected to be highly time‐consuming. Implementing a screening procedure with our hotline questionnaire helped us streamline the donor selection process and reduce the workload for the staff. We propose combining the described selection process with the later introduced on‐site antibody screening as an effective strategy.